THE ESTIMATION OF THE HEIGHT AND HALF-WIDTH OF THE TWILIGHT BEAM IN EARTH ATMOSPHERE - Shakun, L. S. (Одеські астрономічні публікації, 2017)
New program models the scattering of the sun light in Earth atmosphere. The program is not in the strict relation with the model of light scattering and atmosphere structure. This fact permits to use the program for different atmosphere models. The way of determination of the twilight beam characteristics is discussed in detail. The article presents the results of the model for average atmosphere. They may be used for determine of the direction scattering coefficient and execute iterations. The given is model similar to the average model used in N.B. Divari' articles. This fact caused the similarity of the obtained results.